2016
DOI: 10.1007/s00170-016-8366-1
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical studies on the formability of TB5 titanium sheet in rubber cold forming

Abstract: Titanium alloys are often used in aircraft manufacturing. Titanium sheet exhibits low formability and high springback at room temperature, and this causes significant challenges with conventional forming methods. In this study, the phenomena and mechanisms of the formability of TB5 titanium alloys in rubber forming were investigated. It was found that rubber forming was effective for TB5 titanium sheets. Wrinkling in rubber forming was controlled by the side blankholder. The effects of the design parameters of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…These simulation parameters have been optimized and proved to be effective for rubber forming. 22 Many simulations have been done to compare the effects of different parameters on the forming results. The size ranges of the a, b, c, and d are 50°-60°, 5-20 mm, 5-10 mm, and 20-35 mm, respectively.…”
Section: Finite Element Simulationmentioning
confidence: 99%
“…These simulation parameters have been optimized and proved to be effective for rubber forming. 22 Many simulations have been done to compare the effects of different parameters on the forming results. The size ranges of the a, b, c, and d are 50°-60°, 5-20 mm, 5-10 mm, and 20-35 mm, respectively.…”
Section: Finite Element Simulationmentioning
confidence: 99%
“…At present, one of the most common approaches for reducing wrinkles in rubber forming is the side blank holder. Chen et al(2016) investigated the phenomena and mechanisms of the formability of TB5 titanium alloys in rubber forming and found that the largest height of the wrinkles became smaller with the increase of the forming force, while the hardness of the rubber had little effect. Chen et al(2012) conducted finite element analysis of the rubber forming process of high shrinkage bending edges in ABAQUS software, where the results showed that the greater the distance between the side blank holder and the die, the easier the material to wrinkle.…”
Section: Introductionmentioning
confidence: 99%